2019
DOI: 10.1016/j.schres.2017.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive therapy of psychosis: Research and implementation

Abstract: Cognitive therapy for psychosis (CBTp), schizophrenia and psychotic symptoms has advanced rapidly over the past two decades and is having an increasing influence on clinical practice.Research has focused on symptoms, e.g. paranoia, negative symptoms and hallucinations, and stages of the disorder, e.g. early intervention and persistent symptoms. It has used a range of approaches, e.g. brief or lengthier interventions for individual and groups, and in different cultural settings.Recent meta-analyses of studies d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Consequently, as revealed by our study, the significant positive change in the concepts of well-being and hope in the experimental group also seemed to be compatible with hope and psychological well-being studies in relation to schizophrenia in which cognitive techniques have been used in the literature (Lim et al, 2018;Valiente et al, 2019). In earlier studies for interventions for individuals diagnosed with schizophrenia, it was stated that long-term cognitive interventions of 16 to 20 sessions are effective, while shorter sessions were also found to be particularly noteworthy in newer ones (Kingdon & Turkington, 2019). Accordingly, in our study, more information about the literature including new and short-term sessions was provided.…”
Section: Discussionsupporting
confidence: 68%
“…Consequently, as revealed by our study, the significant positive change in the concepts of well-being and hope in the experimental group also seemed to be compatible with hope and psychological well-being studies in relation to schizophrenia in which cognitive techniques have been used in the literature (Lim et al, 2018;Valiente et al, 2019). In earlier studies for interventions for individuals diagnosed with schizophrenia, it was stated that long-term cognitive interventions of 16 to 20 sessions are effective, while shorter sessions were also found to be particularly noteworthy in newer ones (Kingdon & Turkington, 2019). Accordingly, in our study, more information about the literature including new and short-term sessions was provided.…”
Section: Discussionsupporting
confidence: 68%
“…This protocol includes the core components of CBTp described above, and the components are generally consistent with those tested in positive CBTp trials, such as Sensky et al (2000) and A. P. Morrison et al (2018). Goals for the intervention are established by the client in conjunction with the provider and typically include symptom reduction, distress reduction, enhanced coping, progress toward goals, and/or improved functioning and quality of life (Beck et al, 2011;D. Kingdon & Turkington, 2019).…”
Section: Selecting a Cbtp Intervention To Utilizementioning
confidence: 99%
“…134 While more recent thirdwave currents (including acceptance and commitment therapy and mindfulnessbased therapies) 135 offer a less belieffocused orientation, second wave CBT remains the most widely used and researched CBT approach for schizophrenia. 136,137 Overview and discussion of evidence Systematic empirical validation of the efficacy of CBT for schizophrenia started from the 1990s onwards. Early metaanalytic studies found CBT to be modestly effective (effect sizes [Cohen's d] ranging between 0•35 and 0•65) in ameliorating positive symptoms, [138][139][140] hence leading to its recommendation as a treatment of choice alongside antipsychotic medication in both UK and US government guidelines.…”
Section: Cognitive-behavioural Therapy Of Delusion In Schizophreniamentioning
confidence: 99%